Much More Than a Cytoskeletal Protein: Physiological and Pathological Functions of the Non-microtubule Binding Region of Tau - Brandt, Roland; Trushina, Nataliya I.; Bakota, Lidia (Frontiers in Neurology, 2020)
Tau protein (MAPT) is classified as a microtubule-associated protein (MAP) and is believed to regulate the axonal microtubule arrangement. It belongs to the tau/MAP2/MAP4 family of MAPs that have a similar microtubule binding region at their carboxy-terminal half. In tauopathies such as Alzheimer’s disease, tau is distributed more in the somatodendritic compartment, where it aggregates into filamentous structures, the formation of which correlates with cognitive impairments in patients. While microtubules are the dominant interaction partners of tau under physiological conditions, tau has many additional interaction partners that can contribute to its physiological and pathological role. In particular, the amino-terminal non-microtubule binding domain (N-terminal projection region, NTR) of tau interacts with many partners that are involved in membrane organization. The NTR contains intrinsically disordered regions (IDRs) that show a strong evolutionary increase in the disorder and may have been the basis for the development of new, tau-specific interactions. In this review we discuss the functional organization of the tau protein and the special features of the tau non-microtubule binding region also in the connection with the results of Tau KO models. We consider possible physiological and pathological functions of tau's non-microtubule interactions, which could indicate that interactions mediated by tau’s NTR and regulated by far-reaching functional interactions of the PRR and the extreme C-terminus of tau contribute to the pathological processes.